Investigating Source Contributions of Size‐Aggregated Aerosols Collected in Southern Ocean and Baring Head, New Zealand Using Sulfur Isotopes. Issue 8 (16th April 2018) - Li, Jianghanyang; Michalski, Greg; Davy, Perry; Harvey, Mike; Katzman, Tanya; Wilkins, Benjamin
Abstract: Marine sulfate aerosols in the Southern Ocean are critical to the global radiation balance, yet the sources of sulfate and their seasonal variations are unclear. We separately sampled marine and ambient aerosols at Baring Head, New Zealand for 1 year using two collectors and evaluated the sources of sulfate in coarse (1–10 μm) and fine (0.05–1 μm) aerosols using sulfur isotopes (δ 34 S). In both collectors, sea‐salt sulfate (SO4 2− SS ) mainly existed in coarse aerosols and nonsea‐salt sulfate (SO4 2− NSS ) dominated the sulfate in fine aerosols, although some summer SO4 2− NSS appeared in coarse particles due to aerosol coagulation. SO4 2− NSS in the marine aerosols was mainly (88–100%) from marine biogenic dimethylsulfide (DMS) emission, while the SO4 2− NSS in the ambient aerosols was a combination of DMS (73–79%) and SO2 emissions from shipping activities (~21–27%). The seasonal variations of SO4 2− NSS concentrations inferred from the δ 34 S values in both collectors were mainly controlled by the DMS flux. Plain Language Summary: Marine sulfate aerosols are critical to the global radiation balance through directly scattering sunlight or forming clouds; however, their feedback effects are poorly quantified because their sources and size distributions are unclear. We investigated the origins and size distributions of sulfate aerosols from the Southern Ocean as well as the ambient environment at Baring Head, New Zealand. We found that the sulfate in coarse (>1 um) aerosols was dominated by sea‐salt sulfate; while the fine aerosol (<1 um) sulfate, which could act as cloud condensation nuclei, was mostly formed via atmospheric oxidation of sulfur‐bearing gases. The origin of the secondary sulfate was then identified using sulfur isotopic analysis: Dimethylsulfide emitted by phytoplankton contributed over 90% of the secondary sulfate on the Southern Ocean; it also contributed ~73–79% of secondary sulfate aerosols in the ambient air at Baring Head, while the remainder was from anthropogenic sulfur emissions. Our work suggest that marine biological activity is an important factor that controls the amount of sulfate aerosols in remote marine atmosphere, which is of great importance to global climate models. Key Points: Source distribution and seasonal variation of size‐aggregated sulfate aerosols collected at Baring Head, New Zealand were investigated Coarse aerosol sulfate was mainly from sea salt; sulfate in fine aerosols was mostly secondary sulfate Most secondary sulfate was originated from marine DMS emission and should explain the seasonal variations of Southern Ocean CCN